Antibiotic resistance in urinary tract infections: A re-visit after five years and experience over two sites. Issue 2 (June 2020) - Baines, Georgina; Banjoko, Adeolu; Brair, Amalia; Gray, Jim; Desai, Nergish; Cardozo, Linda; Toozs-Hobson, Philip
Objective: The aim of this study was to repeat a previous audit, performed from 2009 to 2013, for the cohort of 2018 to determine how the resistance rates in urinary pathogens in women over 18 years of age have changed. A secondary aim of the study was to use resistance data from a different UK hospital in the same year to compare differences in resistance rates across different geographic locations Study design: This was a retrospective study of all positive urine cultures grown from female patients attending two different hospitals in the year 2018. Resistance patterns were analysed. Results: The resistance rate to co-amoxiclav continues to increase with amoxicillin retaining high resistance patterns. There are some significant differences in resistance patterns between the different locations. Conclusion: Antimicrobial resistance is a significant problem in the UK particularly in antibiotics used to treat UTI. These patterns can vary across different geographical locations and over time; therefore, up-to-date knowledge of local anti-biotic resistance is essential when making an appropriate prescription choice.